Creation and evolution: A relationship fraught with misunderstandings - Rothgangel, Martin (HTS teologiese studies, 2019)
The relationship between evolution and creation, both religiously and ideologically, continues to be a source of misunderstandings that occur at various levels and is further explored in this article. On the basis of empirical studies and theological considerations, the following four types of misunderstandings in the field of religious education are discussed: (1) ‘Creation’ as nature – an ethically motivated misunderstanding, (2) Genesis 1 as ‘Creation Report’ – a theologically conditioned misunderstanding, (3) ‘Scientific Creation Report’ versus Evolution – the Creationist misunderstanding and (4) Scientifically proven Theory of Evolution versus Creation – the Scientistic misunderstanding. These types of misunderstanding might be well known to experts in the field of ‘creation and evolution’. In the field of religious education, however, the harassing question remains as to why these misunderstandings are so widespread and resistant. For this reason, the last part of the articles asserts that empirical teaching and learning research is a religious educational desideratum in the face of these misunderstandings.